Spectrophotometric Method for Monitoring Bioethanol Production in Yeast Cells - Erguden, Bengu (Innovative Scientific Information & Services Network, 2019)
The continuous increase in global energy demand and need necessitates the availability of new energy sources. The expansion of production of bioethanol will reduce our dependence on petroleum and natural gas, and contribute to the decrease of environmental pollution by reducing emission of greenhouse gases. In the course of our studies for bioethanol production we needed a practical and inexpensive method for the extraction of ethanol from fermentation media and determination of the amount of bioethanol produced. We herein report a spectrophotometric method for measurement of ethanol concentration in aqueous solutions which depends on the dichromate oxidation of the ethanol. Furthermore, we applied this method successfully to the determination of amount of bioethanol produced by fermentation in Saccharomyces cerevisiae cells.
Keywords: bioethanol; Saccharomyces cerevisiae; spectrophotometry; dichromate oxidation